Pengaruh Bahan Ajar Berbasis Teknologi pada Pembelajaran IPAS Materi Sifat-sifat Cahaya Terhadap Kemampuan Berpikir Kritis Siswa - Widda Ulinuha; Agie Nurwati; Elsa Chaeratunnisa; Shofia Zahra Agustina; Suroso Mukti Leksono (Postgraduate, University of Mataram, 2024)
The aim of this research is to find out how technology-based teaching materials influence students' critical thinking abilities when studying the properties of light in science. This research is using experimental method. The experimental method was chosen because it allows researchers to control all the variables involved and determine the cause-and-effect relationship between the use of technology-based teaching materials and increasing students' critical thinking abilities. The research results show the effectiveness of using technology-based teaching materials. The statistical table shows that the average post-test score for the experimental class was 81.25, while the control class obtained an average score of 66.88. This indicates that students who learn with technology-based teaching materials have better critical thinking skills compared to students who use conventional learning methods. Thus, there is a significant influence of the use of technology-based teaching materials on students' critical thinking abilities. Implementation of this strategy not only improves learning outcomes but also motivates students through learning methods that are more interesting and relevant to current technological developments.